COMPARATIVE ASSESSMENT OF SUBREGIONAL GROUPINGS OF COUNTRIES FOR EFFECTIVE COMBATING OF FINANCIAL FRAUD AND MONEY LAUNDERING DURING AND AFTER THE WAR IN UKRAINE - ZAKHARKINA, Liudmyla; NEBABA, Natalia; VOITOV, serhii; ROMANOVSKYY, Artur; KASIAN, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article presents a comparative analysis of the potential of three subregional cooperation formats: the Visegrad Group (V4), the Baltic States, and the GUAM Organization for effective combat against financial fraud and money laundering during and after the war in Ukraine. The study examines institutional cooperation mechanisms, the degree of political cohesion among member states, readiness to apply sanction mechanisms, and the capacity for integration into new cooperative formats. It reveals that none of the existing alliances alone ensures comprehensive protection against financial crimes under current crisis conditions. The research highlights the urgent need for the formation of a new coalition of capable states, composed of Ukraine, Poland, Czechia, Lithuania, Latvia, Estonia, Slovakia, Moldova, and Georgia. Such a coalition would foster enhanced information exchange, integration of sanction enforcement efforts, monitoring of international aid dedicated to reconstruction, and prevention of financial crimes in vulnerable environments. It would strategically combine the regulatory strength of EU countries with the operational intelligence and situational awareness of frontline states. The proposed model also emphasizes the importance of flexible coordination structures rather than rigid institutional frameworks, aiming for synergy based on shared risks, mutual interests, and compliance with global anti-money laundering and counter-terrorism financing (AML/CFT) standards. The findings of the study are practically significant for improving the resilience of regional financial security systems, ensuring the transparency of recovery aid flows, and preventing illicit financial activities in both wartime and post-conflict recovery phases. The research contributes to the development of regional strategies that align with global security frameworks and offers valuable recommendations for policymakers, supervisory authorities, and international organizations seeking to enhance coordinated responses to financial crime threats in times of political and economic instability.
Keywords: financial fraud; money laundering; subregional associations; international cooperation; war in Ukraine; post-war recovery